A Cool Approach to Probing Speech Cortex - Flinker, Adeen (Neuron, 2016)
In this issue of Neuron, Long et al. (2016) employ a novel technique of intraoperative cortical cooling in humans during speech production. They demonstrate that cooling Broca’s area interferes with speech timing but not speech quality.